(untitled) (Scientific journal of the Fergana State University, 2026)
This article explores the role and significance of creativity in enhancing the professional competence of future music teachers. Creativity enables educators to implement innovative approaches in the teaching process, thereby improving the quality of education. The paper analyzes methods and practical activities aimed at improving the professional skills of music teachers through the development of creative thinking and innovative strategies. It also discusses strategies for fostering creativity and its positive impact on the educational process. In conclusion, the importance of creativity in overcoming routine tasks and promoting personal and professional growth is emphasized.